CORAL REEF CONDITION IN RELATION TO CORAL REEF FISH ABUNDANCES BEFORE MASS BLEACHING EVENT IN SIMEULUE ISLANDS, ACEH - Ulung Jantama Wisha; Koko Ondara; Wisnu Arya Gemilang; Guntur Adhi Rahmawan; Ruzana Dhiauddin; Ilham Ilham (Indonesian Fisheries Research Journal, 2019)
Bordered with the Indian Ocean, Simeulue Islands is one of the outermost islands in Indonesia located in the west part of Aceh Province. Simeulue waters are productive areas due to the unpolluted condition yet and great of biomass. Three regions were particularly observed, those are Simeuluecut, Ganting, and Labuhan Bajau. In those areas, the existing marine tourism activities might influence the coral reef ecosystem studied. This study aimed to evaluate the condition of coral and coral reef fish in those three particular regions before mass bleaching event in 2016 triggered by ENSO. Point Intercept Transect (PIT) method was employed to record the percentage cover of coral, species diversity, and coral reef fish. Ganting waters was a moderate ecosystem area whith the percentage coverage was up to 45.62%. However, in Simeuluecut and Labuhan Bajau waters, the coral reef communities were excellent with coral percentage coverage reached 83.12% and 81.25 %, respectively. The highest  abundance genera of coral reef fish was observed in Simueluecut waters. This condition was changed oppositely in 2016 when mass bleaching threatened Simeulue waters due to temperature anomaly triggered by ENSO phenomenon. The temperature increases almost 3oC for 6 months that undoubtedly induced bleaching that about 50% of coral colonies were dramatically declined in coral coverage and coral recruitment.